Prognostic Implications and Alterations in Left Atrial Deformation Following Transcatheter Aortic Valve Implantation - Butcher, Steele C.; Hirasawa, Kensuke; Meucci, Maria Chiara; Stassen, Jan; Kuneman, Jurrien H.; Pereira, Ana Rita; van der Kley; Frank; de Weger, Arend; van Rosendael, Philippe J.; Marsan, Nina Ajmone; Playford, David; et al. (Oxford University Press, 2025)
Aims
To evaluate the prognostic implications of the left atrial reservoir strain–defined diastolic dysfunction (LARS-DD) grade in patients undergoing transcatheter aortic valve implantation (TAVI) for severe aortic stenosis (AS) and to determine whether post-TAVI LARS was more closely associated with new-onset atrial fibrillation than pre-TAVI LARS.
Methods and results
Pre-TAVI LARS-DD was evaluated by speckle-tracking echocardiography and was assigned as Grade 0 to 1 (LARS ≥24%), Grade 2 (LARS 19–24%), and Grade 3 (LARS <19%). Patients were followed up for the primary endpoint of all-cause mortality from the date of TAVI. For the secondary endpoint, patients with pre- and post-TAVI LARS measurements and no history of atrial fibrillation were evaluated for the occurrence of new-onset atrial fibrillation. A total of 601 patients [median age 81 (76–85) years, 53% males] were included. Overall, 169 patients (28%) were LARS-DD Grade 0/1, 96 patients (16%) were LARS-DD Grade 2, and 336 (56%) were LARS-DD Grade 3. Over a median follow-up of 40 (interquartile range 26–58) months, a total of 258 (43%) patients died. In a comprehensive multivariable Cox regression model, the LARS-DD grade was independently associated with all-cause mortality [adjusted hazard ratio (HR) 1.28 per one-grade increase, 95% confidence interval (CI) 1.07–1.53, P = 0.007]. For the secondary endpoint of new-onset atrial fibrillation, a total of 285 patients were evaluated. Post-TAVI LARS (subdistributional HR 1.14 per 1% <20%, 95% CI 1.05–1.23, P = 0.0009), but not pre-TAVI LARS (P = 0.93), was independently associated with new-onset atrial fibrillation.
Conclusions
An increased LARS-DD grade was independently associated with long-term post-TAVI survival in patients with severe AS. Post-TAVI LARS was closely related to the occurrence of new-onset atrial fibrillation.